การพัฒนาระบบการทดสอบโดยใช้คอมพิวเตอร์เพื่อการประเมินสมรรถนะการประเมินชั้นเรียนของครู : การประยุกต์ใช้ทฤษฎีการตอบสนองข้อสอบแบบพหุมิติ - ถิรายุ อินทร์แปลง (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This research development was aimed at creating and developing a computer-based testing system. Firstly, developed a framework and description of performance assessment. Secondly, developed a computer-based testing system and examined measure s psychometric properties with discriminant, content structural and concurrent validity, MNSQ, multidimensionality, and item response theory.  Thirdly, assessed the competency of teachers under the Office of the Basic Education Commission and the testing system’s efficacy. The 1,780 samples were used to determine the cut-off points by construct map theory. The findings are as follows. First, the competency framework and description quality passed (Mdn=3.50-5.00, IQR=0.00-1.50). Second, the psychometric properties of the measure met the acceptable with high reliability (rtt=.80-.82) and concurrent validity (rxy=.73). The assessment model was consistent with empirical data (X2=39.461, df=30, p= .116, AGFI=.988, CFI=.989, TLI=.979, SRMR=.019, RMSEA=.016, AIC=60062.182, BIC=60247.748). The OUTFIT MNSQ ranged from .764-.1.199, and The INFIT MNSQ ranged from .787-1.137. Third, the testing system was reasonable and passed (Mdn=5.00, IQR=1.00, M=4.45, SD=0.73).